There’s no place like home: cage odours and place preference in subordinate CD-1 male mice - Fitchett, Ann E.; Barnard, Christopher J.; Cassaday, Helen J. (Elsevier, 2006)
Prior studies using mice have shown that scent marks are an important source of information and can cause behavioural changes in other individuals. Studies have also shown that scent marks in the environment can affect the outcome of social interactions between mice. We used conditioned place preference tests to investigate whether CD-1 male mice (Mus musculus) are reinforced by olfactory cues from the home cage. Soiled bedding from the home cage was presented in the initially less preferred chamber of the apparatus to determine whether this association would reduce the unconditioned preference for one chamber over the other. We tested the effects of social rank and housing condition by comparing the performance of dyads that were polarised into dominant and subordinate relationships, both when paired and when separated, with mice that were isolated throughout. The development of conditioned place preference (CPP) supported by home cage odours was influenced by social rank but not by housing condition. Only subordinate mice showed CPP to home cage odours, and this effect was seen irrespective of whether they were housed with a dominant cage mate or alone. Neither dominant (paired or separated) nor isolated mice showed any change in their preference for the chamber associated with home cage odours. This suggests that the smell of home is a more powerful reinforcer for subordinate mice in that it can produce contextual conditioning to the environment in which it is experienced.